Improved Process Stability on an Extremely Thin Amorphous/Crystalline Silicon Interface Passivation Layer by Using Predeposition on the Chamber Wall. (4th July 2018) - Hsieh, Yu-Lin; Tseng, Ching-Lin; Lee, Chien-Chieh; Fuh, Yiin-Kuen; Chang, Jenq-Yang; Lee, Ju-Yi; Li, Tomi T.
Abstract : In this study, in situ plasma diagnostic systems of optical emission spectrometry (OES) and quadrupole mass spectrometry (QMS) were used to monitor an extremely thin (5–10 nm) intrinsic amorphous/crystalline Si interface passivation film as deposited using plasma-enhanced chemical vapor deposition (PECVD). We observed a dramatic improvement in the quality of the passivation layer with a chamber background environment, even with a background pressure of 1E-6 Torr. When the chamber walls were coated (at a predeposition time of approximately 150 min) to a specified thickness of a few hundred micrometers, the minority carrier lifetime increased by more than 26 times, as compared with an insufficiently coated counterpart with a predeposition of approximately 30 min (from approximately 30 μs to 800 μs). In this predeposition process, the tendency of species to concentrate could be systematically obtained using the in situ OES system, with the chamber environment monitored using residual gas analysis and threshold ionization mass spectrometry of QMS. We found that the optimal predeposition time was 150 min, which enabled the OES intensity of Si * /SiH *, Hβ /Hα, and Hα/SiH * to become stable. OES and QMS were incorporated in this study and were validated using the Fourier-transform infrared spectroscopy absorbance spectra on the films. The plasma condition was stabilized and the minority carrier lifetime was improved to 800 μs. The proposed predeposition process stabilized the chamber environment and gas discharge. Therefore, the optimized value of the minority carrier lifetime could be consistently obtained. A transmission electron microscopy photograph showed a compact a-Si:H layer (of approximately 10 nm) on the c-Si substrate interface passivation layer with a void-free and crystallites-free interface after a predeposition time of 150 min.